Drought-induced mortality in Scots pine: opening the metabolic black box. (21st June 2019) - MacAllister, Sarah; Mencuccini, Maurizio; Sommer, Ulf; Engel, Jasper; Hudson, Andrew; Salmon, Yann; Dexter, Kyle G
Abstract: Forests are sensitive to droughts, which increase the mortality rate of tree species. Various processes have been proposed to underlie drought-induced tree mortality, including hydraulic failure, carbon starvation and increased susceptibility to natural enemies. To give insights into these processes, we assessed the metabolic effects of a mortality-inducing drought on seedlings of Pinus sylvestris L. (Scots Pine), a widespread and important Eurasian species. We found divergence over time in the foliar metabolic composition of droughted vs well-watered seedlings, with the former showing increased abundance of aromatic amino acids and decreases in secondary metabolism associated with defence. We observed no significant differences amongst provenances in these effects: seedlings from drought-prone areas showed the same foliar metabolic changes under drought as seedlings from moist environments, although morphological effects of drought varied by provenance. Overall, our results demonstrate how severe drought prior to death may target particular primary and secondary metabolic pathways, weakening defences against natural enemies and contributing to the risk of drought-induced mortality in P. sylvestris .